Adsorption of pb(ii) on Durian leaves / Rabihah Awang Ali and Zurhana Mat Hussin - Awang Ali, Rabihah; Mat Hussin, Zurhana (Universiti Teknologi MARA Cawangan Pahang, 2019)
In order to reveal the performance of Durian Leaves (DL) as a putatively advantageous biosorbent for the removal of Pb(II) from aqueous solution, the kinetic of biosorption, and the physio-chemical factors on biosorption were investigated comprehensively. DL was characterized by using pHslurry and pHpzc of biosorbent. The effect of physicochemical such as pH, adsorbent dosage, initial concentration of Pb(II) and contact time has been studied to obtain the optimum condition to remove Pb(II) ion from the aqueous solution. The studies were conducted at pH 4, DL dosage 0.04 g, and in contact time of 90 minutes. Kinetic data were analyzed by using two adsorption kinetic models which are pseudo-first-order and pseudosecond-order. The data shows high correlation coefficient based on pseudo-second-order model with R2 is 0.9905 rather than pseudo-first-order model. Our results demonstrate that the DL is a promising biomass-based biosorbent for the removal of Pb(II) from wastewater for its fine capacity of biosorption